The Effect of Empowering Leadership, Perceived Organizational Support, And Job Demands on Work Engagement Through Work Fatigue As A Mediating Variable - Abdel Muammar Rafi Muzakki; Dewi Susita; Widya Parimita (International Journal Labs, 2026)
Maintaining employee engagement is particularly important in project-based construction, where productivity and organizational continuity depend on employees who can remain attentive and committed despite heavy workloads, strict deadlines, safety obligations, and operational complexity. This study investigates how empowering leadership, perceived organizational support, and job demands are related to work engagement, with work fatigue examined as a mediating mechanism. The respondents were employees of PT Hutama Karya (Persero) Infrastructure Division I assigned to MRT CP 203, NPEA Section 1, the Jakarta Sewerage Development Project (JSDP), and Huntara Senen in the Greater Jakarta area. The research applied a quantitative explanatory design with cross-sectional data from 182 purposively selected employees. Responses to 57 questionnaire items were analyzed in SmartPLS 4 using Partial Least Squares Structural Equation Modeling (PLS-SEM), a reflective-reflective hierarchical component model, and the disjoint two-stage procedure. The estimates indicate that empowering leadership and perceived organizational support are positively associated with work engagement and negatively associated with work fatigue. Job demands show the opposite pattern, with a negative relationship to work engagement and a positive relationship to work fatigue. Work fatigue is also negatively related to engagement and carries complementary partial mediation for each of the three exogenous constructs. The results highlight the need for project organizations to develop empowering supervisors, provide credible organizational support, regulate excessive demands, and establish sufficient opportunities for employee recovery.